Display of the pres regions of the surface antigen of Hepatitis B virus on M13 and T7 Bactetiophages - Kok, Wai Ling (2001)
Hepatitis B virus (HBV) is the prototype of the family Hepadnaviridae, which causes liver disease in humans, mammals and birds. The envelope of HBV contains three related surface antigens (termed L-, M- and S-HBsAg) produced by alternative initiation of translation in a single coding region. These polypeptides harbour a common 226 amino acids at their C-terminus, which is also the entire length of the S-HBsAg. The M-HBsAg contains an N-terminal extension of 55 amino acids known as the PreS2 region. The longest of the three, L-HBsAg, has the PreS 1 region of 108 or 119 amino acids (depending on serotype) followed by the PreS2 and the S regions. The PreS domain is believed to be involved in virion assembly and attachment to a hepatocyte receptor during infection. In order to study the functions of this region, the PreS and PreS 1 domains were fused to the g3p protein of bacteriophage Ml3 and lOB protein of bacteriophage T7, respectively, that allow the fusion proteins to be displayed. The PreS-g3p fusion protein produced in a suppressor strain of Escherichia coli was detected by the antiE tag antibody with a size of approximately 66 kDa on a Western blot. In a nonsuppressor strain of E. coli, the soluble PreS protein was detected in the medium, periplasm and cytoplasm with a molecular mass of approximately 22 kDa. Meanwhile in the T7 system, the first and second halves of PreS 1 were detected by the T7 Tag antibody on a Western blot with a size of around 50 kDa. The functional display of the PreS region would provide an alternative means to study its interactions with the nucleocapsid and hepatocytes. Precise definition of the regions and specific amino acids in L-HBsAg that are required for efficient interaction with the nucleocapsid and hepatocytes, may help to identify lead compounds for therapeutic agents based upon inhibition of viral morphogenesis.